Penggunaan Bantuan Operasional Sekolah (Bos) Oleh Kepala Sekolah Dalam Pengembangan Sarana Prasarana Di SDN 01 Seloromo Kabupaten Karanganyar - Widyaningsih, Arista; , Minsih, S.Ag, M.Pd (2017)
This study aims to determine the use of school operational funds (BOS), describes the rules, constraints and solutions to overcome the principal obstacles in the use of the School Operational Assistance (BOS) in the development of facilities and infrastructure at SDN 01 Seloromo. This study used a qualitative approach with descriptive qualitative research design. This research was conducted at SDN 01 Seloromo from September 2016 to January 2017. Data collection techniques used were interviews, observation and documentation. Data analysis it is included data reduction, data presentation, and conclusion. Based on the results of this study concluded that the use of the School Operational Assistance (BOS) includes planning, implementation, monitoring and evaluation, and reporting of the School Operational Assistance (BOS). The main priority refers to the 13 items of expenditure. Barriers often happens is the delay in the disbursement of School Operational Assistance (BOS). Solutions to overcome obstacles is to make use of other funding sources for example funds from the Central Government, Local Government, SSN funding, school cooperative and voluntary contributions from parents and the community.